Innovation in dementia education within undergraduate healthcare programmes: A scoping review. (March 2021) - Williams, Matthew; Daley, Stephanie
Abstract: Objectives: The increase in the number of people living with dementia has resulted in a greater need for healthcare professionals from all disciplines to meet the needs of those living with the condition. This means a workforce which is competent in delivering dementia care which is person-centred, regardless clinical specialism. The aim of scoping review is to provide an overview of the novel education models being used to ensure the future healthcare workforce are able to meet this aspiration. Data sources: Online databases PubMed, Web of Science, CINAHL, Medline, PsychInfo, ERIC were used. Review methods: Search terms 'Healthcare Student(s)', 'Dementia or Alzheimer's Education' were used. Inclusion criteria included papers published in English between 2009 and September 2019, with data pertaining to the assessment of dementia knowledge and attitudes among healthcare students . Abstracts were reviewed and identified for inclusion for full-text review. Included studies were assessed using the MMAT (Mixed Methods Appraisal Tool). Results: 27 studies were included within the review. These were groups into five educational categories; long term experiential ( n =5), activity-centered programmes with people with dementia ( n =11), interprofessional education (IPE) ( n =5), immersive conference style programmes ( n =3) and dementia simulation (n=3). Long term experiential and activity centered programmes gave students the greatest increase in perceived confidence, and improvement in dementia attitudes. Programmes were most effective when directly involving people living with dementia. Conclusion: The majority of the education programmes showed a potential benefit in improving either knowledge, confidence, attitude, or all three among healthcare students. This highlights the benefit that novel experiential programmes may have in aiding a culture of positive attitudes among future healthcare professionals who will be treating people with dementia. This review also demonstrates the positive benefit that directly involving people living with dementia within education can have on both student learners. Highlights: Overview of innovation in undergraduate dementia education over the last decade Demonstrates the increasing involvement of people with dementia and their carers in undergraduate healthcare education Gives prominence to the emergence of creative activity-based learning with students and people with dementia